Growth after War in Syria - Devadas, Sharmila; Elbadawi, Ibrahim; Loayza, Norman V. (World Bank, Washington, DC, 2019)
This paper addresses three questions: 1) what would have been the growth and income trajectory of Syria in the absence of war; 2) given the war, what explains the reduction in economic growth in terms physical capital, labor force, human capital, and productivity; and 3) what potential growth scenarios for Syria there could be in the aftermath of war. Estimates of the impact of conflict point to negative gross domestic product (GDP) growth of -12 percent on average over 2011-18, resulting in a GDP contraction to about one-third of the 2010 level. In post-conflict simulation scenarios, the growth drivers are affected by the assumed levels of reconstruction assistance, repatriation of refugees, and productivity improvements associated with three plausible political settlement outcomes: a baseline (Sochi-plus) moderate scenario, an optimistic (robust political settlement) scenario, and a pessimistic (de facto balance of power) scenario. Respectively for these scenarios, GDP per capita average growth in the next two decades is projected to be 6.1, 8.2, or 3.1 percent, assuming that a final and stable resolution of the conflict is achieved.